North Dublin Regional DATF Alcohol Research 2023 An exploration of the nature and extent of alcohol use within North County Dublin - Ivers, Jo-Hanna (My University, 2024)
The North Dublin Regional Drug & Alcohol Task Force was established in 2003 under the National Drug Strategy. It is one of 10 regional Task Forces in the country. It brings key stakeholders together to coordinate an evidence informed and health led drug and alcohol strategy in the North Dublin Region. In the last decade the Task Force ramped up its efforts to reduce alcohol related harm. It partnered with Ballymun and Finglas Local DATFs to implement CARE; a community alcohol treatment model which yielded positive externally evaluated outcomes. Furthermore, the Task Force continues to deliver a schedule of SAOR training in its area, community awareness of alcohol harm, health promotion with partners in HSE Health and Wellbeing and Healthy Fingal and a range of other programmes. In 2023, the Task Force established its first ‘sober social club’ in its Inclusion Hub in Balbriggan which has gone from strength to strength and its team continues to provide alcohol specific treatment, CRA, CBT and other interventions for people in the area. It also recognises hidden harm through specialist supports for family members including: 5 step, PUP, Mindfulness stress relief, Triple P and others. The Task Force opened its WISE service in Balbriggan, with its first ever WISE Worker in 2023 to provide a gender specific service for women. Through its partnership working it has delivered evidence‐based alcohol interventions for individuals, families and the wider community from prevention, early intervention right through to treatment, rehabilitation, and aftercare. Alcohol continues to be our primary drug presentation in our community‐based services. Indeed, since the writing of this report new alcohol treatment episodes captured in the latest HRB data for people living here increased by 26%. These figures only capture new treatment cases rather than prevalence so significantly underestimate the real scale of the problem. Furthermore the 2023 whole population data captured in the school’s survey of nearly 3000 children for our region shows an increase in binge drinking among those aged 14‐16years; an increase by 3% in children accessing alcohol directly from parents or an adult known to them; and 67% now citing parents are against them being drunk compared to 72% in 2021. While the Task Force has always placed a great emphasis on data to inform responses, this research report is important in helping us understand the nature of alcohol use and the factors that are likely to help us address it. To that end, this report is the most comprehensive alcohol research undertaken in the area to date.
PUBLISHED
Keywords: Alcohol use, Ireland, Dublin; Alcoholism, Ireland, Dublin; Alcohol abuse, Ireland, Dublin